A Wearable Iron-Based Implant as an Intramedullary Nail in Tibial Shaft Fracture of Sheep - Sitaria F. Siallagan; Marzuki Silalahi; Arief Boediono; Sri Estuningsih; Deni Noviana (International Journal of Biomaterials)
A stable repaired fracture is the key factor responsible for the recovery of a damaged bone. The iron-based implant is one of the biodegradable metals that have been proven safe as a fracture fixation device. The objective of our experimental approach was to examine the potential of the iron-based implant as a biodegradable metal in tibia shaft fracture in sheep chronically. The samples used for this experiment were iron-based and stainless steel implants. Each had a diameter of 5 mm. These samples were analyzed through 3 phases which are material characterization, in vitro and in vivo examination. The samples were examined using a scanning electron microscope with energy dispersive spectrometer and X-ray diffraction. Based on the analysis carried out, the samples contained 90,02% and 60,81% Fe for iron-based implant and stainless implant, respectively. Both implants maintained high viability when being in contact with calf pulmonary artery endothelial cells, indicating that both implants had a minimum response to the cell in a hemocytometer and methyl tetrazolium (MTT) assay. The systemic effect of the implants was observed using hematology and blood chemistry examination. Data collection also shows that both implants also had a minimum response to the erythrocytes, leucocytes, blood chemistry, and blood mineral during the period of observation. Therefore, it could be concluded that the iron-based implant is tolerable for a period of 9 months. It also has the potential to be used as a biodegradable orthopedic implant.